Analysis and approximation for the performance of a workstation with various types of setups - Wu, Kan (2020)
Setups commonly exist in flexible manufacturing systems. Modelling the queue time correctly is of fundamental importance in evaluating the performance of manufacturing systems. An insightful classification is the first step towards correct modelling. Through the observation of practical production lines, two types of setups are classified: state-induced setups and product-induced setups. The product-induced setups can be a changeover setup or a replacement setup. Changeover setups are induced by switching manufacturing processes between products, whereas replacement setups are caused by changing components or consumables. Approximate models for the mean queue time of different setup types are proposed based on their distinct properties. The proposed models are validated with simulations and perform well in the examined cases.